2020
DOI: 10.5194/essd-12-947-2020
|View full text |Cite
|
Sign up to set email alerts
|

New continuous total ozone, UV, VIS and PAR measurements at Marambio, 64° S, Antarctica

Abstract: Abstract. A ground-based ultraviolet (GUV) multi-filter radiometer was set up at Marambio, 64∘ S, 56∘ W, Antarctica, in 2017. The instrument continuously measures ultraviolet (UV) radiation, visible (VIS) radiation and photosynthetically active radiation (PAR). The measurements are designed for providing high-quality long-term time series that can be used to assess the impact of global climate change in the Antarctic region. The quality assurance includes regular absolute calibrations and solar comparisons per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Over the open ocean, increased UV radiation in spring and summer compared to winter may lead to greater NO₃⁻ production from the photolytically derived oceanic RONO2 source (Fisher et al, 2018). Ground-based studies at various Antarctic sites demonstrate that UV radiation increases throughout spring and is highest in early summer (Lakkala et al, 2020;Li et al, 2020). This, in addition to greater lightning NOx production during spring and summer at the lower southern latitudes (< 40 ⁰S) (Nesbitt et al, 2000) likely explain why higher [NO₃⁻] are observed in spring and summer as compared to winter.…”
Section: Seasonal Variation In Atmospheric No₃⁻ Concentrationsmentioning
confidence: 99%
“…Over the open ocean, increased UV radiation in spring and summer compared to winter may lead to greater NO₃⁻ production from the photolytically derived oceanic RONO2 source (Fisher et al, 2018). Ground-based studies at various Antarctic sites demonstrate that UV radiation increases throughout spring and is highest in early summer (Lakkala et al, 2020;Li et al, 2020). This, in addition to greater lightning NOx production during spring and summer at the lower southern latitudes (< 40 ⁰S) (Nesbitt et al, 2000) likely explain why higher [NO₃⁻] are observed in spring and summer as compared to winter.…”
Section: Seasonal Variation In Atmospheric No₃⁻ Concentrationsmentioning
confidence: 99%
“…This region has very few measurements of solar UV irradiance and shows extreme UVI throughout the year. In the context of climate change, this region of the world (Southern Hemisphere tropics) could be affected by a decrease in ozone and an increase in UV radiation levels throughout the 21st century (Lamy et al, 2019). UV-Indien measurement sites correspond to various environments (seaside, altitude, urban) and are homogeneously distributed throughout the western Indian Ocean.…”
Section: Ground-based Reference Datamentioning
confidence: 99%
“…For comparison, level 3 data with 0.25 • resolution from the Ozone Monitoring Instrument (OMI) on board the Aura satellite (Levelt et al, 2018), received through the NASA Giovanni interface (https://giovanni.gsfc.nasa.gov/giovanni/, last access: 14 June 2019), were used. Daily values of the OMI ozone product co-located with the Marambio station (64.125 • S, 56.625 • W for OMI data) were used and the ratio of daily ozone values (OMI / GUV) was calculated.…”
Section: Total Column Ozone Measurementsmentioning
confidence: 99%